ANALYSIS OF THE HALAL STATUS OF MARINE PRODUCTS FROM CORPORATE PRODUCTION PROCESSES AND ISLAMIC LEGAL PERSPECTIVES - Siregar, Emiel Salim; Apdilah, Dicky (Proceeding International Seminar of Islamic Studies, 2024)
Illegal fishing means all forms of fishing activities that violate Law Number 31 of 2004 article 1 and other laws and regulations that are still in force as well as in Islamic law as stated in the Al-Qur'an Surah Ar Rum verse 30 which says that It has been seen that damage on land and at sea is caused by the actions of human hands; Allah wants them to experience some of the (consequences of) their actions, so that they return (to the right path). Say (Muhammad), “travel the earth and see what happened to the people of old. Most of them are people who oppose (Allah).” (Q.S. Ar Rum (30): From this verse it is clear that Allah SWT forbids His servants from doing damage on earth and in the sea. The act of fishing continuously and using tools that damage the marine environment can be categorized as a criminal act (jinayah) if the act meets criminal elements. As in Islamic law, there are three elements that must be fulfilled if a person's actions can be categorized as criminal acts. The obstacles faced by corporations regarding the fish production process in accordance with Islamic law have not yet been met for the distribution/distribution of fishery products, namely the principle of balance and the principle of responsibility. This is shown by fisheries entrepreneurs when their fish is ready to be harvested and distributed/distributed, they have to wait first, because the distributors prioritize family property and even their own, for the losses experienced by fisheries entrepreneurs they are not responsible for what they have done. agreed. Another obstacle in fishing is still a lack of awareness, both from fishermen who work to entrepreneurs in the fisheries sector or fisheries entrepreneurs who do not care about good fishing methods that are not prohibited, such as in accordance with the teachings of Islamic law, in a halal way, starting from catching, management to fish production. Later the processed fish will be bought and sold and consumed by the community.